The effect of religiosity and spirituality on financial behavior district - Endi, Anjelina Christi; Fanggidae, Rolland E.; Ndoen, Wehelmina M. (Goodwood Publishing, 2023)
Purpose: This study was conducted on the members of KSP Kopdit Permata Bunda Paroki Waelengga. This study aims to determine the effects of religiosity and spirituality on the financial behavior of the members of Kopdit Permata Bunda Paroki Waelengga. Research methodology: This study used a quantitative approach and survey method. The population in this study comprised all Kopdit Permata Bunda members. This study used Simple Random Sampling with a total sample of 100 members. The primary data source was collected using a direct survey in the field that was distributed using a questionnaire to KSP Kopdit Permata Bunda Paroki Waelengga members. Data analysis techniques were used with simple linear regression using SPSS software version 16.0. Results: The results showed that the religiosity variable had a positive relationship but no significant effect on the variables of financial behavior, the spirituality variable had a positive relationship but no significant effect on the variables of financial behavior, and the variables religiosity and spirituality together had a positive relationship but no significant effect on the variables of financial behavior. Conclusions: The study concludes that religiosity and spirituality, while important aspects of personal values, are not sufficient predictors of financial behavior among cooperative members. Financial decisions appear to be shaped more by economic, social, and educational factors than by gender. Limitations: This study was limited to one cooperative institution and two variables, with a relatively small sample size. Contribution: This research contributes to the behavioral finance literature by contextualizing the role of religiosity and spirituality in financial behavior, offering insights for cooperatives and policymakers in designing member education programs.